Upper extremity posture and muscle activity during IV pole interaction. Issue 2 (2nd April 2020) - Forman, Garrick N.; Breitner, Victoria; Shivpaul, Ryan; Murczek, Donna; Holmes, Mike W.R.
Abstract : Background . The physical demands associated with patient handling activities have been well documented in healthcare. However, many activities contribute to the physical demands of caregivers. Our purpose was to evaluate upper extremity muscle activity and kinematics during intravenous (IV) pole interaction. Materials and methods . Muscle activity was measured from six muscles using surface electromyography and joint kinematics were measured using motion capture. Participants performed two IV pole tasks: loading an IV bag and a medical device onto the pole. Two poles were evaluated: a traditional IV pole and a redesigned pole with ergonomic considerations. Results . Cervical extensor activity was significantly greater for the bag task with the traditional pole (43.29 ± 5.10% maximal voluntary exertion) compared to the redesigned pole (28.55 ± 3.42% maximal voluntary exertion). Peak right shoulder flexion was reduced from 102.88° ± 32.42° with the traditional pole to 55.44° ± 19.59° with the redesigned pole. Conclusion . Interactions with a traditional pole are comparable to upper extremity muscle activity during manual patient handling transfers. The redesigned pole reduced shoulder flexion during bag attachment, leading to less time in an overhead posture. Caregivers frequently interact with IV poles and reducing the physical demands associated with pole use could aid in a reduction of musculoskeletal disorders.